2023
DOI: 10.1002/moda.2
|View full text |Cite
|
Sign up to set email alerts
|

Selenium in modern agriculture

Abstract: Selenium (Se) is a micronutrient necessary in small amounts for the proper organism functioning. Se‐rich agriculture, also known as special agriculture, has the potential to improve agricultural production and produce beneficial agricultural products. This review discusses the various applications of Se in agriculture, including animal husbandry, crop production and aquaculture. It covers Se metabolites, the function and regulation of selenogenomes and selenoproteomes of human and animal food and the recycling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 94 publications
1
1
0
1
Order By: Relevance
“…The application of Se also increased the rice biomass in this study, while the transcriptome analysis showed that the DEGs were enriched in the glutathione metabolic pathway and flavonoid biosynthesis pathway. This is consistent with previous findings that Se can stimulate the production of secondary metabolites in plants and increase their tolerance to stress, which affects the uptake of Se by the roots ( Feng et al., 2021 ; Huang et al., 2023 ). Sun et al.…”
Section: Discussionsupporting
confidence: 93%
“…The application of Se also increased the rice biomass in this study, while the transcriptome analysis showed that the DEGs were enriched in the glutathione metabolic pathway and flavonoid biosynthesis pathway. This is consistent with previous findings that Se can stimulate the production of secondary metabolites in plants and increase their tolerance to stress, which affects the uptake of Se by the roots ( Feng et al., 2021 ; Huang et al., 2023 ). Sun et al.…”
Section: Discussionsupporting
confidence: 93%
“…Останніми роками у багатьох країнах світу переглядаються, із урахуванням нових наукових даних, уже існуючі норми введення мікроелементів у комбікорми для високопродуктивних кросів і порід сільськогосподарської птиці. Це стосується й Селену, який сьогодні визнаний незамінним біотичним мікроелементом (Huang et al, 2023).…”
Section: вступunclassified
“…Furthermore, we have published a Perspective article discussing the posibility of cutting respiratory CO 2 to sustain crop productivity and manage atmospheric carbon, 3 a Commentary article on a recent breakthrough in vertical farming, 4 and several Reviews, and other articles covering topics, such as modern forestry, 5 smart breeding, 6 carbon-nitrogen interplay, 7 and selenium in modern agriculture. 8 There are various article types for the authors to choose including Original Research articles that report on new scientific findings, Resource articles that provide useful resources or tools for agricultural research or practice, Review/Perspectives that provide an overview or analysis of a particular topic or field related to agriculture, Correspondence that respond to or comment on previously published articles, Commentary that presents the author's opinion or perspective on a particular issue related to agriculture, News and Views that report on recent developments or news related to agriculture, and Patent articles that report on new patents related to agricultural innovations. More article types and explanations are available in the Author Guidelines.…”
mentioning
confidence: 99%